Preparation method of nanocrystallization precursor of high-compaction-density lithium iron phosphate
By grinding and preparing the secondary reaction mother liquor during the synthesis of lithium iron phosphate precursors, the problem of difficult particle size and morphology is solved, production costs and wastewater treatment pressure are reduced, and lithium iron phosphate precursors with high compaction density and excellent electrochemical properties are achieved.
Patent Information
- Application Number
- CN202411762875.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-04-18
AI Technical Summary
During the synthesis of lithium iron phosphate precursors, the particle size distribution and morphology are difficult to control, the high raw material cost, the large amount of water generated by mother liquor and washing water leads to large water treatment pressure, and the large phosphorus loss during crystallization.
By grinding during the beating stage, the secondary particle size of the material before crystallization is controlled, so that the material to be crystallized can achieve uniform particle nanoification, and grinding is carried out during the crystallization process to block the generation of regenerated large particles. Use the secondary reaction mother liquor and phosphoric acid to prepare the beating base liquid in a certain proportion to reduce wastewater discharge. The aged iron phosphate dihydrate is dried and depolymerized by a butterfly nest mill, and after sintering, a high-pressure density lithium iron phosphate precursor is obtained.
The precise control of the particle size and morphology of the lithium iron phosphate precursor is achieved, which reduces production costs, reduces wastewater treatment pressure, and improves the compaction density and electrochemical properties of the material.
Smart Images

Figure CN119841290A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for preparing a lithium iron phosphate precursor with high compaction density, and in particular to a method for preparing a precursor of a battery-grade lithium iron phosphate positive electrode material. Background Art
[0002] As the global demand for new energy sources grows, lithium-ion batteries are widely used in electric vehicles, energy storage systems and other fields due to their high energy density, long cycle life and environmental protection. Among them, lithium iron phosphate is considered to be one of the most promising lithium-ion battery cathode materials due to its abundant raw materials, low price and good safety performance.
[0003] Lithium iron phosphate (LiFePO4) has the advantages of high energy density, long cycle life and low production cost. It is widely used in electric vehicle batteries, energy storage battery systems and other fields. With the increasing competition in the electric vehicle market, low-cost and high-performance electric vehicles have become the mainstream development direction of the market. As the core component of batteries, battery cost reduction and performance improvement are also extremely important. For the high endurance requirements of electric vehicles, targeted development of high-density and high-energy-density cathode materials means that the battery can provide more energy per unit volume; for the low-cost preparation requirements of batteries, targeted development of low-cost raw materials is also the main direction of cost reduction. Therefore, the development of low-cost and high-performance lithium iron phosphate has become the development direction of the new energy materials industry. As the main front-end raw material of the cathode material, iron phosphate determines the performance of lithium iron phosphate materials on the one hand, and also affects the price of the material on the other hand. Therefore, it is necessary to prepare low-cost iron phosphate through the iron phosphate process to reduce the cost. In addition, it is of great significance to improve the electrochemical properties of lithium iron phosphate by developing a method that can prepare a high-density, small-particle-size and uniform lithium iron phosphate precursor.
[0004] The main methods for preparing iron phosphate include coprecipitation method, hydrothermal method, sol-gel method, etc. These methods usually require complex equipment and strict condition control, and are costly. At the same time, these methods are often difficult to achieve precise control of the particle size and morphology of the lithium iron phosphate precursor, which may affect the electrochemical properties of the final lithium iron phosphate. In terms of production process, conventional production processes usually require the use of a large amount of water and energy, which not only increases production costs, but also puts pressure on the environment. Secondly, these methods are often difficult to achieve precise control of the particle size and morphology of the lithium iron phosphate precursor, which may affect the electrochemical properties of the final lithium iron phosphate. In addition, these methods may generate a large amount of waste gas and wastewater during the preparation process, causing pollution to the environment. Finally, these methods have low production efficiency and are difficult to meet the needs of large-scale production. The present invention aims to solve the problems of difficult control of particle size distribution and morphology during the synthesis of lithium iron phosphate precursors, high raw material costs, large water volume generated by mother liquor and wash water, resulting in high water treatment pressure, and large phosphorus loss during crystallization. Summary of the invention
[0005] In order to achieve the above-mentioned purpose, the present invention proposes a method for preparing a high compaction density lithium iron phosphate precursor: the specific technical scheme includes: (1) grinding in the pulping stage to control the secondary particle size of the material before crystallization after pulping, so that the material to be crystallized can achieve uniform particle nano-crystallization, and grinding is performed simultaneously in the crystallization process to control the size of the slurry particles and induce crystal transformation to block the growth of large regenerated particles and break the uncontrollable regeneration mode; (2) the secondary reaction mother liquor and phosphoric acid are used to prepare a pulping base liquid in a certain proportion for the pulping stage, which can reduce the amount of wastewater discharged, and the microparticle seeds in the mother liquor can induce crystal transformation; (3) the aged dihydrate iron phosphate is dried and depolymerized by a butterfly nest mill to control the moisture and particle size, and anhydrous iron phosphate is obtained after sintering and screening. Thereby, the final iron phosphate has good consistency, high stability, and low production cost, and the lithium iron phosphate material finally prepared by using the iron phosphate has a high compaction density.
[0006] To achieve the above objectives, the present invention provides a method for preparing a high compaction density lithium iron phosphate precursor, which specifically comprises the following steps: (1) Add a certain amount of pure water into a ferrous preparation kettle, add high-purity ferrous sulfate in a certain proportion, start stirring and heating to stir and dissolve, and filter the ferrous solution after it is completely dissolved to obtain a ferrous sulfate solution; (2) Mixing diammonium phosphate solution and ammonia water or phosphoric acid and ammonia water in proportion to prepare a uniform and stable pH adjuster; (3) The ferrous sulfate solution of step (1) is quantitatively added into a specific reactor, 85% phosphoric acid (i.e., phosphoric acid with a mass fraction of 85%) is added to form an acidic ferric phosphate dihydrate solution (the acidic ferric phosphate dihydrate solution refers to a pH of 1.0-1.4), and high-purity oxygen is introduced into the bottom of the reactor at a flow rate of 10-20 Nm 3 / h, and at the same time, a pH regulator is added into the reactor at a specific speed by a peristaltic pump, stirring is started to carry out an oxidation synthesis reaction, the reactor is kept in a slightly positive pressure state, the pressure in the reactor is adjusted, and oxygen is recovered and processed at the top of the reactor for recycling. After the pH regulator is added, the reaction is continued for 90-120 minutes to form a primary reaction slurry; (4) Filter and wash the reaction slurry in step (3) until the conductivity is 10-15ms / cm, and then continue to wash with pure water until the conductivity is 1-3ms / cm. Unload the filter cake into a ball mill slurry kettle, add phosphoric acid for slurry grinding, grind the slurry to 50-500nm, switch the valve to the aging kettle for crystallization, heat the aging kettle to 90-95℃, and the high temperature heating rate is 20-30s / ℃. At the same time, circulate the slurry in the aging kettle to the ball mill for grinding. By adjusting the grinding frequency, the particle growth and particle morphology are controlled in a directional manner during the aging process. The particles of the aging slurry are in a dissolution process during the heating stage, so low-frequency 10-20Hz ball milling is performed. The particles are in a growth process during the insulation stage after discoloration, so the external circulation slurry frequency is 30-45HZ, and the insulation after discoloration is 90-120min. In this stage, the external circulation grinding is improved to control the secondary particle size of the slurry after the primary reaction, so that the material to be crystallized can achieve uniform particle nano-crystallization, and effectively control the morphology and size distribution of the initial crystallization process of the material. The cyclic material grinding during the crystallization process breaks the inherent uncontrollable regeneration mode, blocks the generation of large particles during the regeneration process, and effectively reduces the agglomeration and adhesion phenomenon during the crystallization regeneration process. The microstructure of the prepared secondary iron phosphate dihydrate particles is dense and uniform.
[0007] In some embodiments, the ball milling frequency is dynamically adjusted between 30-45 Hz during the ball milling slurrying process to ensure that the particle size is between 500-1000 nm, and more preferably, the particle size is between 800-1000 nm.
[0008] In some embodiments, the mother liquor B in step (5) is also added to step (4) and slurry grinding is performed simultaneously. The slurrying process uses the recycled mother liquor as the slurrying base liquid, effectively utilizes the phosphorus in the mother liquor, and reasonably introduces the microparticle seeds in the mother liquor. The microparticle seeds in the mother liquor can induce crystal transformation in the crystallization stage, thereby improving the crystal transformation efficiency.
[0009] (5) The amorphous flaky iron phosphate slurry after aging and heat preservation is filtered to obtain filter cake and mother liquor A. After collecting mother liquor A, the mother liquor A is concentrated using a reverse osmosis membrane. The mother liquor A and phosphoric acid are prepared according to the comparison, and then the washing water of the iron phosphate dihydrate filter cake is added and stirred to obtain mother liquor B. The phosphorus content in mother liquor B is 0.4%-0.5%. The filter cake is washed with pure water to a washing conductivity of 0.4-0.8ms / cm, and all the washing water is collected and mixed evenly to obtain washing water B.
[0010] (6) The washed amorphous flaky iron phosphate is dried, depolymerized, and finely ground using a butterfly nest mill to obtain dihydrate iron phosphate with a qualified particle size distribution, and finally sintered at high temperature in a rotary kiln. After cooling, a nano-sized precursor of lithium iron phosphate with a high compaction density is obtained.
[0011] The high temperature drying equipment is a butterfly nest mill, the air outlet is 90-105°C, the moisture content of the dihydrate ferric phosphate after drying is <2000ppm, the particle size D50 of the dihydrate ferric phosphate after depolymerization is 2-4um, and the high temperature sintering temperature equipment is a rotary kiln, and the sintering temperature is 560-580°C.
[0012] During the drying stage of the dihydrate iron phosphate, a butterfly nest mill is used for drying, depolymerization and crushing to control the initial particle size distribution of the sintered material. After sintering, the particle size of the anhydrous iron phosphate is directly within the qualified range, and the mechanical grinding and crushing process can be deleted, which reduces the post-processing time and equipment investment and realizes lean production. The secondary particles of iron phosphate prepared in this way have a dense and uniform microstructure, and the primary particles are small and uniform. The lithium iron phosphate positive electrode material prepared by the iron phosphate generated by this patented process has a very high compaction density.
[0013] Beneficial effects of the present invention: 1. The present invention adopts oxygen oxidation synthesis, utilizes the dynamic movement of gas to increase the collision probability between the iron source and the phosphorus source, and effectively increases the nucleation efficiency of the synthesis process with high-speed stirring, thereby accelerating the reaction speed.
[0014] 2. The recycling of oxygen in the synthesis process of the present invention can ensure that the excess oxygen can fully oxidize the ferrous iron, while effectively controlling the emission of oxygen and the increase in cost.
[0015] 3. The crystallization process of the present invention increases the ball milling external circulation and high temperature crystallization simultaneously to make the microstructure of the lithium iron phosphate precursor particles dense and uniform, effectively control the generation of large particles in the crystallization process, and reduce the agglomeration and adhesion phenomenon of the crystallization process regeneration.
[0016] 4. The present invention controls the secondary particle size of the sintered material through primary reaction, crystallization reaction grinding particle control, and butterfly nest grinding and breaking up during the drying process, so that the secondary particle size of the sintered material is basically within the qualified index, without the need for pulverization, simplifying the process and reducing equipment investment.
[0017] 5. The preparation method of the present invention has high yield, is suitable for large-scale production, and meets the needs of large-scale production.
[0018] 6. The preparation method of the present invention generates less waste gas and waste water during the preparation process, and the secondary washing water and mother liquor are processed and utilized, so the resource utilization rate is high and the environmental pollution is small.
[0019] In this preparation process, the nucleation and growth rates of the primary reaction are reasonably controlled by using a special feeding method and matching high-speed stirring. This process can directly and effectively recycle the phosphorus-containing secondary reaction mother liquor and wash water to the pulping stage after treatment. This solution alleviates the pressure of wastewater treatment by reducing wastewater generation, while reducing the input of phosphoric acid and pure water to reduce the cost of raw materials. This process reduces production costs while reducing environmental pollution. The slurrying process uses the recycled mother liquor as the slurrying base liquid, effectively utilizes the phosphorus in the mother liquor, and reasonably introduces the crystal seeds of the microparticles in the mother liquor. In the crystallization stage, the microparticle seeds in the mother liquor can induce crystal transformation and improve the crystal transformation efficiency. In the pulping stage, the external circulation grinding is improved to control the secondary particle size of the slurry after the primary reaction, so that the material to be crystallized can achieve uniform particle nano-crystallization, and effectively control the morphology and size distribution of the initial crystallization process of the material. The grinding of circulating materials in the crystallization process breaks the inherent uncontrollable regeneration mode, blocks the generation of large particles in the regeneration process, and effectively reduces the agglomeration and adhesion phenomenon in the crystallization regeneration process. The prepared secondary particles of iron phosphate dihydrate have a dense and uniform microstructure. In the drying stage of iron phosphate dihydrate, a butterfly nest mill is used for drying and re-depolymerization and crushing to control the initial particle size distribution of the sintered material. After sintering, the particle size of anhydrous iron phosphate is directly within the qualified range, and the mechanical grinding and crushing process can be deleted, reducing post-processing time and equipment investment, and realizing lean production. The secondary particles of iron phosphate prepared in this way have a dense and uniform microstructure, and the primary particles are small and uniform. The lithium iron phosphate positive electrode material prepared by the iron phosphate generated by this patented process has a very high compaction density. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is the SEM of the ferric phosphate product obtained in Example 1 of the present invention.
[0021] Figure 2 This is the SEM of the ferric phosphate product obtained in Example 2 of the present invention.
[0022] Figure 3 This is the SEM of the ferric phosphate product obtained in Example 3 of the present invention.
[0023] Figure 4 This is the SEM of the ferric phosphate product obtained in Example 4 of the present invention.
[0024] Figure 5This is the SEM of the ferric phosphate product obtained in Example 5 of the present invention.
[0025] Figure 6 SEM of lithium iron phosphate prepared from the iron phosphate product obtained in Example 1 of the present invention.
[0026] Figure 7 The XRD of the iron phosphate product obtained in Example 1 of the present invention.
[0027] Figure 8 Process flow chart of the present invention. DETAILED DESCRIPTION
[0028] The endpoints and any values of the ranges disclosed in the present invention are not limited to the exact ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in the present invention.
[0029] In order to better understand the present invention, the content of the present invention is further described below in conjunction with embodiments and related drawings, but the content of the present invention is not limited to the following embodiments.
[0030] The main raw material information is as follows: Ammonia NH3·H2O (22%-26%), 35.05g / mol, prepared by liquid ammonia and ammonia generator, produced by the company; hydrogen peroxide H2O2 (26%-35%), 34.01g / mol, produced by the company; refined phosphoric acid H3PO4 (84%-86%), 98g / mol, produced by the company; ferrous sulfate heptahydrate FeSO4·7H2O (95-99%), 278.01g / mol, Shanghai McLean Biochemical Technology Co., Ltd.
[0031] The impurity element test of the ferrous sulfate heptahydrate is as follows: Table 1
[0032] Example 1 (1) Preparation of ferrous sulfate solution: Add 0.998 m³ of pure water (conductivity < 5 μS / cm) into a ferrous sulfate dissolving kettle, weigh 365.0 kg of ferrous sulfate heptahydrate, and stir to fully dissolve it. The heating temperature is 60°C and the stirring speed is 80 rpm. After complete dissolution for 10 minutes, filter it with a precision filter to obtain a clear ferrous solution.
[0033] (2) Preparation of pH adjuster: Add 0.4m³ of pure water (conductivity <5 μS / cm) into the dropping tank, weigh 45.0kg of refined phosphoric acid and add it into the dropping tank, weigh 341.7kg of 24% ammonia water and slowly add it into the dropping tank, start high-speed stirring at 200rmp, start the circulating water cooling system to control the solution temperature to 30-40℃, react for ten minutes after the ammonia water is added, and the pH adjuster is prepared.
[0034] (3) Preparation of synthetic base liquid: Add the ferrous solution after dissolution and filtration into the reactor, weigh 104.7 kg of refined phosphoric acid and add it into the reactor, start stirring at 100 rpm for 30 minutes, ensure that the initial temperature is 25-35°C, and make the pH value 1.2-1.3.
[0035] (4) Oxidation synthesis reaction: Start high-speed stirring at 200 rpm, introduce high-purity oxygen to the bottom of the reactor, control the oxygen flow rate to 20 Nm³ / h, and collect and recycle the introduced oxygen at the top of the reactor. After introducing oxygen for 5 minutes, start the peristaltic pump of the dropping tank, and add the pH adjuster evenly into the reactor using the atomizing nozzle. Control the addition time to 30 minutes, maintain the reactor in a slightly positive pressure state, control the reaction endpoint temperature to 40-60°C, and the reaction endpoint pH to 2.0±0.5. After the addition is completed, continue to introduce oxygen and start stirring to allow the solution to continue to fully react for 90 minutes.
[0036] (5) Washing of the primary reaction: The slurry after the oxidation reaction is filtered into a filter press. After the material is filtered, it is pre-pressed to completely discharge the mother liquor. Then, the filter cake of the primary reaction is washed with pure water. The conductivity at the end point of washing is 1 ms / cm.
[0037] (6) Grinding and slurrying: Add the qualified filter cake after one washing into the slurrying kettle, start the slurrying and grinding, grind the slurry particles to a particle size of 500 nm, and then switch the valve to input the slurry into the aging kettle. At the same time, in a complete preparation process, add 1.4 m³ of the mother liquor B treated in step (8) into the slurrying kettle for slurrying.
[0038] (7) Ball milling heating aging: Turn on the aging kettle heating system and heat the material in the aging kettle to 95°C at a heating rate of 2°C / min. During the heating process, turn on the slurry ball milling external circulation system of the aging kettle to carry out aging and ball milling simultaneously. During the heating stage, use low frequency 10-20Hz for ball milling. After the temperature rises to 95°C, that is, during the high temperature stage, use high frequency 30-45Hz for ball milling. About 10 minutes after reaching the temperature, the slurry turns white. After the color changes, continue to use high frequency ball milling for 90 minutes during the insulation stage to ensure that the slurry particle size is in the range of 800-1000nm. During the insulation process, test the slurry particle size every ten minutes. If it is higher than this range, keep the high frequency 30-45Hz for ball milling. If it is lower than this range, adjust to low frequency 10-20Hz for ball milling.
[0039] (8) Secondary reaction washing: The aging slurry was water-cooled to 60°C and then transported to a filter press. The secondary reaction mother liquor was collected by filtering and pre-pressing. The mother liquor was concentrated to obtain mother liquor A. The phosphorus content of the supernatant of mother liquor A was measured to be 3000ppm. 16.4 kg of refined 85 phosphoric acid was weighed and added to mother liquor A. The mother liquor was stirred at high speed. The settled particles and the added phosphoric acid were evenly mixed with mother liquor A to obtain mother liquor B. The secondary reaction filter cake was washed with pure water. The conductivity at the washing end point was 0.1 ms / cm and the pH value of the washing water end point was 2.5.
[0040] (9) Turn on the butterfly nest mill and control the outlet air temperature to 90°C. Dry, depolymerize and finely grind the filter cake after washing to obtain dry ferric phosphate dihydrate. By controlling the depolymerization frequency of the butterfly nest mill, the particle size is controlled to be D50 < 5 μm, D100 < 50 μm, and the moisture content is < 1000 ppm.
[0041] (10) After drying, the dihydrate iron phosphate was sintered at high temperature in a rotary kiln at 580°C for 3 h to obtain anhydrous iron phosphate. Lithium iron phosphate positive electrode material was prepared using anhydrous iron phosphate as iron and phosphorus sources, lithium carbonate as lithium source, glucose and PEG as carbon sources, and titanium dioxide as dopant. Finally, the positive electrode material was crushed and tested for powder compaction and electrochemical properties.
[0042] Example 2 (1) Preparation of ferrous sulfate solution: Add 0.998 m³ of pure water (conductivity < 5 μS / cm) into a ferrous sulfate dissolving kettle, weigh 365.0 kg of ferrous sulfate heptahydrate, and stir to fully dissolve it. The heating temperature is 60°C and the stirring speed is 80 rpm. After complete dissolution for 10 minutes, filter it with a precision filter to obtain a clear ferrous solution.
[0043] (2) Preparation of pH adjuster: Add 0.4m³ of pure water (conductivity <5 μS / cm) into the dropping tank, weigh 45.0kg of refined phosphoric acid and add it into the dropping tank, weigh 341.7kg of 24% ammonia water and slowly add it into the dropping tank, start high-speed stirring at 200rmp, start the circulating water cooling system to control the solution temperature to 30-40℃, react for ten minutes after the ammonia water is added, and the pH adjuster is prepared.
[0044] (3) Preparation of synthetic base liquid: Add the ferrous solution after dissolution and filtration into the reactor, weigh 104.7 kg of refined phosphoric acid and add it into the reactor, start stirring at 100 rpm for 30 minutes, ensure that the initial temperature is 25-35°C, and make the pH value 1.2-1.3.
[0045] (4) Oxidation synthesis reaction: Start high-speed stirring at 200 rpm, introduce high-purity oxygen to the bottom of the reactor, control the oxygen flow rate to 20 Nm³ / h, and collect and recycle the introduced oxygen at the top of the reactor. After introducing oxygen for 5 minutes, start the peristaltic pump of the dropping tank, and add the pH adjuster evenly into the reactor using the atomizing nozzle. Control the addition time to 30 minutes, control the reaction endpoint temperature to 40-60°C, and the reaction endpoint pH to 2.0±0.5. After the addition is completed, continue to introduce oxygen and start stirring to allow the solution to continue to fully react for 90 minutes.
[0046] (5) Washing of the primary reaction: The slurry after the oxidation reaction is filtered into a filter press. After the material is filtered, it is pre-pressed to completely discharge the mother liquor. Then, the filter cake of the primary reaction is washed with pure water. The conductivity at the end point of washing is 1 ms / cm.
[0047] (6) Grinding and slurrying: Add the qualified filter cake after one washing into the slurrying kettle, start the slurrying and grinding, grind the slurry particles to a particle size of 500 nm, and then switch the valve to input the slurry into the aging kettle. At the same time, in a complete preparation process, add 1.4 m³ of the mother liquor B treated in step (8) into the slurrying kettle for slurrying.
[0048] (7) Ball mill heating aging: Turn on the aging kettle heating system and heat the material in the aging kettle to 95°C at a heating rate of 1-3°C / min. During the heating process, turn on the aging kettle slurry ball milling external circulation system to allow aging and ball milling to proceed simultaneously. During the heating stage, ball milling is performed at a constant low frequency of 20Hz. The slurry turns white about 10 minutes after reaching the temperature. After the color changes, the low-frequency ball milling cycle is continued for 90 minutes during the insulation stage. (8) Secondary reaction washing: The aging slurry was water-cooled to 60°C and then transported to a filter press. The secondary reaction mother liquor was collected by filtering and pre-pressing. The mother liquor was concentrated to obtain mother liquor A. The phosphorus content of the supernatant of mother liquor A was measured to be 3000ppm. 16.4 kg of refined 85 phosphoric acid was weighed and added to mother liquor A. The mother liquor was stirred at high speed. The settled particles and the added phosphoric acid were evenly mixed with mother liquor A to obtain mother liquor B. The secondary reaction filter cake was washed with pure water. The conductivity at the washing end point was 0.1 ms / cm and the pH value of the washing water end point was 2.5.
[0049] (9) Turn on the butterfly nest mill and control the outlet air temperature to 90°C. Dry, depolymerize and finely grind the filter cake after washing to obtain dry ferric phosphate dihydrate. By controlling the depolymerization frequency of the butterfly nest mill, the particle size is controlled to be D50 < 5 μm, D100 < 50 μm, and the moisture content is < 1000 ppm.
[0050] (10) After drying, the dihydrate iron phosphate was sintered at high temperature in a rotary kiln at 580°C for 3 h to obtain anhydrous iron phosphate. Lithium iron phosphate positive electrode material was prepared using anhydrous iron phosphate as iron and phosphorus sources, lithium carbonate as lithium source, glucose and PEG as carbon sources, and titanium dioxide as dopant. Finally, the positive electrode material was crushed and tested for powder compaction and electrochemical properties.
[0051] Example 3 (1) Preparation of ferrous sulfate solution: Add 0.998 m³ of pure water (conductivity < 5 μS / cm) into a ferrous sulfate dissolving kettle, weigh 365.0 kg of ferrous sulfate heptahydrate, and stir to fully dissolve it. The heating temperature is 60°C and the stirring speed is 80 rpm. After complete dissolution for 10 minutes, filter it with a precision filter to obtain a clear ferrous solution.
[0052] (2) Preparation of pH adjuster: Add 0.4m³ of pure water (conductivity <5 μS / cm) into the dropping tank, weigh 45.0kg of refined phosphoric acid and add it into the dropping tank, weigh 341.7kg of 24% ammonia water and slowly add it into the dropping tank, start high-speed stirring at 200rmp, start the circulating water cooling system to control the solution temperature to 30-40℃, react for ten minutes after the ammonia water is added, and the pH adjuster is prepared.
[0053] (3) Preparation of synthetic base liquid: Add the ferrous solution after dissolution and filtration into the reactor, weigh 104.7 kg of refined phosphoric acid and add it into the reactor, start stirring at 100 rpm for 30 minutes, ensure that the initial temperature is 25-35°C, and make the pH value 1.2-1.3.
[0054] (4) Oxidation synthesis reaction: Start high-speed stirring at 200 rpm, introduce high-purity oxygen to the bottom of the reactor, control the oxygen flow rate to 20 Nm³ / h, and collect and recycle the introduced oxygen at the top of the reactor. After introducing oxygen for 5 minutes, start the peristaltic pump of the dropping tank, and add the pH adjuster evenly into the reactor using the atomizing nozzle. Control the addition time to 30 minutes, maintain the reactor in a slightly positive pressure state, control the reaction endpoint temperature to 40-60°C, and the reaction endpoint pH to 2.0±0.5. After the addition is completed, continue to introduce oxygen and start stirring to allow the solution to continue to fully react for 90 minutes.
[0055] (5) Washing of the primary reaction: The slurry after the oxidation reaction is filtered into a filter press. After the material is filtered, it is pre-pressed to completely discharge the mother liquor. Then, the filter cake of the primary reaction is washed with pure water. The conductivity at the end point of washing is 1 ms / cm.
[0056] (6) Grinding and slurrying: Add the qualified filter cake after one washing into the slurrying kettle, start the slurrying and grinding, reduce the grinding efficiency and relax the grinding standard, grind the slurry particles to a size of 1um-1.5um, then switch the valve to input the slurry into the aging kettle. At the same time, in a complete preparation process, add 1.4m³ of treated mother liquor C (different from mother liquor B, the microparticle seeds in the mother liquor are not added) into the slurrying kettle.
[0057] (7) Direct heating aging: Turn on the aging kettle heating system and heat the material in the aging kettle to 95°C at a heating rate of 1-3°C / min. During the heating process, the particle size of the aged slurry is not controlled, and the crystallization process is carried out in a free regeneration manner. The slurry turns white about 35 minutes after reaching the temperature. After the color changes, continue to keep warm and ball mill for 90 minutes.
[0058] (8) Secondary reaction washing: The aging slurry was water-cooled to 60°C and then transported to a filter press. The secondary reaction mother liquor was collected by filtering and pre-pressing. The mother liquor was concentrated to obtain mother liquor A. The phosphorus content of the supernatant of mother liquor A was measured to be 3000ppm. 16.4 kg of refined 85 phosphoric acid was weighed and added to mother liquor A. The mother liquor was stirred at high speed. After stirring, the particles in mother liquor A were filtered and removed using an ultra-precision filter to obtain mother liquor C. The secondary reaction filter cake was washed with pure water. The conductivity at the washing end point was 0.1 ms / cm, and the pH value of the washing water end point was 2.5.
[0059] (9) Turn on the butterfly nest mill and control the outlet air temperature to 90°C. Dry, depolymerize and finely grind the filter cake after washing to obtain dry ferric phosphate dihydrate. By controlling the depolymerization frequency of the butterfly nest mill, the particle size is controlled to be D50 < 5 μm, D100 < 50 μm, and the moisture content is < 1000 ppm.
[0060] (10) After drying, the dihydrate iron phosphate was sintered at high temperature in a rotary kiln at 580°C for 3 h to obtain anhydrous iron phosphate. Lithium iron phosphate positive electrode material was prepared using anhydrous iron phosphate as iron and phosphorus sources, lithium carbonate as lithium source, glucose and PEG as carbon sources, and titanium dioxide as dopant. Finally, the positive electrode material was crushed and tested for powder compaction and electrochemical properties.
[0061] Example 4 (1) Preparation of ferrous sulfate solution: Add 0.998 m³ of pure water (conductivity < 5 μS / cm) into a ferrous sulfate dissolving kettle, weigh 365.0 kg of ferrous sulfate heptahydrate, and stir to fully dissolve it. The heating temperature is 60°C and the stirring speed is 80 rpm. After complete dissolution for 10 minutes, filter it with a precision filter to obtain a clear ferrous solution.
[0062] (2) Preparation of pH adjuster: Add 0.4m³ of pure water (conductivity <5 μS / cm) into the dropping tank, weigh 45.0kg of refined phosphoric acid and add it into the dropping tank, weigh 341.7kg of 24% ammonia water and slowly add it into the dropping tank, start high-speed stirring at 200rmp, start the circulating water cooling system to control the solution temperature to 30-40℃, react for ten minutes after the ammonia water is added, and the pH adjuster is prepared.
[0063] (3) Preparation of synthetic base liquid: Add the ferrous solution after dissolution and filtration into the reactor, weigh 104.7 kg of refined phosphoric acid and add it into the reactor, start stirring at 100 rpm for 30 minutes, ensure that the initial temperature is 25-35°C, and make the pH value 1.2-1.3.
[0064] (4) Oxidation synthesis reaction: Start high-speed stirring at 200 rpm, introduce high-purity oxygen to the bottom of the reactor, control the oxygen flow rate to 20 Nm³ / h, and collect and recycle the introduced oxygen at the top of the reactor. After introducing oxygen for 5 minutes, start the peristaltic pump of the dropping tank, and add the pH adjuster evenly into the reactor using the atomizing nozzle. Control the addition time to 30 minutes, maintain the reactor in a slightly positive pressure state, control the reaction endpoint temperature to 40-60°C, and the reaction endpoint pH to 2.0±0.5. After the addition is completed, continue to introduce oxygen and start stirring to allow the solution to continue to fully react for 90 minutes.
[0065] (5) Washing of the primary reaction: The slurry after the oxidation reaction is filtered into a filter press. After the material is filtered, it is pre-pressed to completely discharge the mother liquor. Then, the filter cake of the primary reaction is washed with pure water. The conductivity at the end point of washing is 1 ms / cm.
[0066] (6) Stirring and slurrying: Add the qualified filter cake after one washing into the slurrying kettle, start stirring for slurrying, set the stirring frequency to high frequency 45 Hz (the stirring upper limit is 50 Hz), and do not control the particle size of the slurry material. After stirring for 20 minutes, the slurry is input into the aging kettle. In a complete preparation process, 1.4 m³ of the mother liquor C treated in step (8) (different from the mother liquor B, the microparticle seeds in the mother liquor are not added) is added to the slurrying kettle.
[0067] (7) Ball mill heating aging: Turn on the aging kettle heating system and heat the material in the aging kettle to 95°C at a heating rate of 1-3°C / min. During the heating process, turn on the slurry ball mill external circulation system of the aging kettle to carry out aging and ball milling simultaneously. No quantitative control is performed on the ball milling particle size standard. The ball milling frequency is fixed at 20Hz to allow the crystallization process material to undergo a fixed frequency and speed ball milling external circulation. The slurry turns white about 35 minutes after reaching the temperature. After the color changes, the heat preservation ball milling cycle continues for 90 minutes.
[0068] (8) Secondary reaction washing: The aging slurry was water-cooled to 60°C and then transported to a filter press. The secondary reaction mother liquor was collected by filtering and pre-pressing. The mother liquor was concentrated to obtain mother liquor A. The phosphorus content of the supernatant of mother liquor A was measured to be 3000ppm. 16.4 kg of refined 85 phosphoric acid was weighed and added to mother liquor A. The mother liquor was stirred at high speed. After stirring, the particles in mother liquor A were filtered and removed using an ultra-precision filter to obtain mother liquor C. The secondary reaction filter cake was washed with pure water. The conductivity at the washing end point was 0.1 ms / cm, and the pH value of the washing water end point was 2.5.
[0069] (9) Turn on the butterfly nest mill and control the outlet air temperature to 90°C. Dry, depolymerize and finely grind the filter cake after washing to obtain dry ferric phosphate dihydrate. By controlling the depolymerization frequency of the butterfly nest mill, the particle size is controlled to be D50 < 5 μm, D100 < 50 μm, and the moisture content is < 1000 ppm.
[0070] (10) After drying, the dihydrate iron phosphate was sintered at high temperature in a rotary kiln at 580°C for 3 h to obtain anhydrous iron phosphate. Lithium iron phosphate positive electrode material was prepared using anhydrous iron phosphate as iron and phosphorus sources, lithium carbonate as lithium source, glucose and PEG as carbon sources, and titanium dioxide as dopant. Finally, the positive electrode material was crushed and tested for powder compaction and electrochemical properties.
[0071] Example 5 (1) Preparation of ferrous sulfate solution: Add 0.998 m³ of pure water (conductivity < 5 μS / cm) into a ferrous sulfate dissolving kettle, weigh 365.0 kg of ferrous sulfate heptahydrate, and stir to fully dissolve it. The heating temperature is 60°C and the stirring speed is 80 rpm. After complete dissolution for 10 minutes, filter it with a precision filter to obtain a clear ferrous solution.
[0072] (2) Preparation of pH adjuster: Add 0.4m³ of pure water (conductivity <5 μS / cm) into the dropping tank, weigh 45.0kg of refined phosphoric acid and add it into the dropping tank, weigh 341.7kg of 24% ammonia water and slowly add it into the dropping tank, start high-speed stirring at 200rmp, start the circulating water cooling system to control the solution temperature to 30-40℃, react for ten minutes after the ammonia water is added, and the pH adjuster is prepared.
[0073] (3) Preparation of synthetic base solution: Add the ferrous solution after dissolution and filtration into the reactor, weigh 104.7 kg of refined phosphoric acid and add it into the reactor, start stirring at 100 rpm for 30 minutes, ensure that the initial temperature is 25-35°C and the pH is 1.2-1.3.
[0074] (4) Oxidation synthesis reaction: Start high-speed stirring at 200 rpm, introduce high-purity oxygen to the bottom of the reactor, control the oxygen flow rate to 20 Nm³ / h, and collect and recycle the introduced oxygen at the top of the reactor. After introducing oxygen for 5 minutes, start the peristaltic pump of the dropping tank, and add the pH adjuster evenly into the reactor using the atomizing nozzle. Control the addition time to 30 minutes, maintain the reactor in a slightly positive pressure state, control the reaction endpoint temperature to 40-60°C, and the reaction endpoint pH to 2.0±0.5. After the addition is completed, continue to introduce oxygen and start stirring to allow the solution to continue to fully react for 90 minutes.
[0075] (5) Washing of the primary reaction: The slurry after the oxidation reaction is filtered into a filter press. After the material is filtered, it is pre-pressed to completely discharge the mother liquor. Then, the filter cake of the primary reaction is washed with pure water. The conductivity at the end point of washing is 1 ms / cm.
[0076] (6) Stirring and slurrying: Add 1.4m³ of pure water into the slurrying kettle, weigh 32.2kg of refined 85 phosphoric acid and add it into the slurrying kettle, add the qualified filter cake after one washing into the slurrying kettle, start stirring for slurrying, set the stirring frequency to high frequency 45Hz (the upper limit of stirring is 50Hz), do not control the particle size of the slurry material, stir for 20min and then input the slurry into the aging kettle.
[0077] (7) Direct heating aging: Turn on the aging kettle heating system and heat the material in the aging kettle to 95°C at a heating rate of 1-3°C / min. During the heating process, the particle size of the aged slurry is not controlled, and the crystallization process is carried out in a free regeneration manner. The slurry turns white about 45 minutes after reaching the temperature. After the color changes, continue to keep warm and ball mill for 90 minutes.
[0078] (8) Secondary reaction washing: The aging slurry is cooled by water to 60°C and then transported to a filter press. The secondary reaction mother liquor is collected by filtration and pre-squeezing. The mother liquor is treated with water and the secondary reaction filter cake is washed with pure water. The conductivity at the washing end point is 0.1 ms / cm and the pH value of the washing water end point is 2.5.
[0079] (9) Turn on the butterfly nest mill and control the outlet air temperature to 90°C. Dry, depolymerize and finely grind the filter cake after washing to obtain dry ferric phosphate dihydrate. By controlling the depolymerization frequency of the butterfly nest mill, the particle size is controlled to be D50 < 5 μm, D100 < 50 μm, and the moisture content is < 1000 ppm.
[0080] (10) After drying, the dihydrate iron phosphate was sintered at high temperature in a rotary kiln at 580°C for 3 h to obtain anhydrous iron phosphate. Lithium iron phosphate positive electrode material was prepared using anhydrous iron phosphate as iron and phosphorus sources, lithium carbonate as lithium source, glucose and PEG as carbon sources, and titanium dioxide as dopant. Finally, the positive electrode material was crushed and tested for powder compaction and electrochemical properties.
[0081] After the iron phosphate materials of Examples 1-5 were synthesized into lithium iron phosphate by the same process, the positive electrode materials were crushed and tested for carbon content, powder compaction density and withholding test.
[0082]
[0083] The above embodiments are only examples for clear explanation, and are not intended to limit the implementation methods. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here, so the obvious changes or modifications derived are still within the protection scope of the invention.
Claims
1. A method for preparing a nano-sized precursor of high compaction density lithium iron phosphate, characterized in that: The steps include: (1) mixing ferrous sulfate and phosphoric acid to form an acidic iron-phosphorus mixed solution, and placing the mixed solution in a reaction kettle; (2) introducing oxygen into the reactor, adding a pH adjuster into the reactor, and stirring to carry out an oxidation synthesis reaction; (3) filtering, washing, and ball-milling the slurry solution synthesized in step (2) and then performing a crystallization stage. During the crystallization stage, ball milling and high temperature reaction are used to perform crystallization nucleation growth. By controlling the particle morphology in the crystallization stage, qualified crystallized particles are obtained and then heat-insulated to obtain aqueous ferric phosphate dihydrate slurry; (4) filtering the completely crystallized aqueous ferric phosphate dihydrate slurry to obtain a ferric phosphate dihydrate filter cake and a mother liquor, and washing and dehydrating the ferric phosphate dihydrate filter cake to obtain an amorphous flaky ferric phosphate dihydrate; (5) The amorphous flaky iron phosphate dihydrate is dried, sintered and sieved to obtain a nano-sized precursor of lithium iron phosphate with high compaction density.
2. The method for preparing a nano-sized precursor of high compaction density lithium iron phosphate according to claim 1, characterized in that: The pH value of the acidic iron-phosphorus mixed solution described in step (1) is in the range of 0.5-1.1, and the Fe:P ratio of the acidic iron-phosphorus mixed solution is 1:0.7; the Fe content in the acidic iron-phosphorus mixed solution is 5%-6%.
3. The method for preparing a nano-sized precursor of lithium iron phosphate with high compaction density according to claim 1, characterized in that: In step (2), the pH adjusting agent is a mixture of any one or two of phosphoric acid and ammonia water, industrial diammonium phosphate and ammonia water, industrial monoammonium phosphate and ammonia water, wherein N:P in the solution is 6-6.5:1, and the pH value is adjusted to 8.5-10.
4. The method for preparing a nano-sized precursor of lithium iron phosphate with high compaction density according to claim 3, characterized in that: In step (2), the oxygen purity is ≥99%; the oxygen inlet flow rate is 10-20Nm³ / h.
5. The method for preparing a nano-sized precursor of lithium iron phosphate with high compaction density according to claim 1, characterized in that: In step (3), the material is ball-milled to control the particle size D50 to be 50-500 nm.
6. The method for preparing a nano-sized precursor of lithium iron phosphate with high compaction density according to claim 1, characterized in that: In the crystallization stage in step (3), the frequency is dynamically adjusted according to the temperature. The low frequency of the external circulation ball milling slurry during the crystallization heating stage is 10-20HZ, the high frequency during the insulation stage after color change is 30-45Hz, the high temperature heating rate is 20-30s / ℃, and the aging temperature is 93-100℃.
7. The method for preparing a nano-sized precursor of lithium iron phosphate with high compaction density according to claim 1, characterized in that: In the ball milling slurry process, the ball milling frequency is dynamically adjusted to ensure that the particle size is between 500-1000nm, and more preferably, the particle size is between 800-1000nm.
8. The method for preparing a nano-sized precursor of lithium iron phosphate with high compaction density according to claim 1, characterized in that: The mother liquor in step (4) is subjected to sedimentation and concentration to obtain mother liquor A; After the mother liquor A and phosphoric acid are prepared according to the comparison, the washing water of the dihydrate iron phosphate filter cake is added and stirred to obtain the mother liquor B. The phosphorus content in the mother liquor B is 0.4%-0.5%.
9. The method for preparing a nano-sized precursor of lithium iron phosphate with high compaction density according to claim 7, characterized in that: The mother solution B is added to step (3) for crystallization.
10. The method for preparing a nano-sized precursor of lithium iron phosphate with high compaction density according to claim 1, characterized in that: In step (5), the high temperature drying equipment is a butterfly nest mill, the air outlet is 90-105°C, the moisture content of the dihydrate ferric phosphate after drying is less than 2000ppm, the particle size D50 of the dihydrate ferric phosphate after depolymerization is 2-4um, and the high temperature sintering temperature equipment is a rotary kiln, and the sintering temperature is 560-580°C.
Citation Information
Patent Citations
Preparation method of iron phosphate with adjustable specific surface
CN116902943A
Iron phosphate material with dense sections, preparation method of iron phosphate material and application of iron phosphate material in preparation of lithium iron phosphate
CN117049491A
Precursor iron phosphate of high-compaction-density lithium iron phosphate material as well as preparation method and application of precursor iron phosphate
CN117800301A
Preparation method of lithium iron phosphate precursor with high electrical property
CN118026122A
Preparation method of iron phosphate precursor adaptive to high-compaction lithium iron phosphate
CN118702083A